Financing pediatric hospital child abuse teams in 2015: National survey results. (May 2023) - Peeler, Elizabeth; Dakil, Suzanne; Culotta, Paige; Giardino, Angelo; Greeley, Christopher; Bachim, Angela
Abstract: Background: Data available on the economics of medical child protection teams stems from prior surveys delivered in 2008 and 2012. Objective: The objective was to describe the current financing strategies of medical child maltreatment groups for benchmarking purposes. Additionally, we aimed to quantify often difficult to measure child abuse services that provide value to pediatric hospitals. Participants and setting: In 2017, a 115-item survey was distributed to 230 pediatric hospitals inquiring about child abuse services for the 2015 calendar year. Methods: The financial topics including budget, revenue, reimbursement, expenses, research, education, and community partnership were analyzed using descriptive statistics. Previous data from similar surveys deployed in 2008 and 2012 were used when applicable to formulate trends. Results: One hundred and thirteen children's hospitals responded comprising a response rate of 49 %. One hundred and four hospitals provided child abuse services at some level. Sixty-two programs (26 %) responded to items about budget. Overall, average team operating budgets increased from $1.15 million in 2008 to $1.4 million in 2015. Few clinical services rendered received full reimbursement. Valuable non-clinical services were poorly reimbursed. An average of 5.45 funding sources were used to supplement remunerations. Conclusion: Child maltreatment teams within pediatric hospitals provide services that are largely unfunded as they are not currently recognized by healthcare payment models. These specialists perform a variety of clinical and non-clinical responsibilities that are critical to the care of this population while relying on a variety of funding sources to support their efforts. Highlights: Child maltreatment medical teams continue to remain value driven. This study provides updated financial benchmark data from calendar year 2015. This report measures non-clinical child abuse services that provide value to pediatric hospitals.